Retrospective Study on Intra-cervical Fistula and the Preferable Routes of Repair - Begum, Bilkis; Sumaiya, A (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Genitourinary fistula has a devastating impact on women’s health. In the developing countries, the most common cause is obstetrical which may occur following obstructed labor or operative injury. The study was designed to analyze 13 rare cases of intra-cervical fistula and preferable routes of repair. The study period was from December 2013 up to November 2021 at four different hospitals in Bangladesh. A standard data collection sheet was used to record important pre, per and post-operative information. All 13 cases were multipara and were delivered by caesarean section. Approaches to repair the fistula were vaginally and abdomino-vaginally. All the 13 cases were primarily closed successfully. The conclusion is that although the vaginal route is preferred in most of the cases but the route of repair should be determined by accessibility of the fistula tract. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(1): 24-27